Efficient callus formation and plant regeneration are heritable characters in sugar beet (Beta vulgaris L.). (December 2016) - Kagami, Hiroyo; Taguchi, Kazunori; Arakawa, Takumi; Kuroda, Yosuke; Tamagake, Hideto; Kubo, Tomohiko
Abstract Background Obtaining dedifferentiated cells (callus) that can regenerate into whole plants is not always feasible for many plant species. Sugar beet is known to be recalcitrant for dedifferentiation and plant regeneration. These difficulties were major obstacles for obtaining transgenic sugar beets through anAgrobacterium -mediated transformation procedure. The sugar beet line 'NK-219mm-O' is an exceptional line that forms callus efficiently and is easy to regenerate, but the inheritance of these characters was unknown. Another concern was whether these characters could coexist with an annual habitat that makes it possible to breed short life-cycle sugar beet suitable for molecular genetic analysis. Findings Five sugar beet lines including NK-219mm-O were crossed with each other and subjected to in vitro culture to form callus. F1 s with a NK-219mm-O background generally formed callus efficiently compared to the others, indicating that efficient callus formation is heritable. The regeneration potential was examined based on the phenotypes of calli after placement on regeneration medium. Five phenotypes were observed, of which two phenotypes regenerated shoots or somatic embryo-like structures. Vascular differentiation was evident in regenerable calli, whereas non-regenerable calli lacked normally developed vascular tissues. In a half-diallel cross, the callus-formation efficiency and the regeneration potential of reciprocal F1 s progeny having a NK-219mm-O background were high. Finally, we crossed NK-219mm-O with an annual line that had a poor in vitro performance. The callus-formation efficiency and the regeneration potential of reciprocal F1 were high. The regenerated plants showed an annual habitat. Conclusions Efficient callus formation and the high plant regeneration potential of NK-219mm-O were inherited and expressed in the F1 . The annual habitat does not impair these high in vitro performances.